A gastric outlet thickened mucosal fold associated with cytomegalovirus infection in an extremely preterm infant managed by surgical resection. (2nd January 2022) - Tangirala, Susmitha; Amboiram, Prakash; Balakrishnan, Umamaheswari; Sundaram, Sandhya; Agarwal, Prakash; Devi, Usha
ABSTRACT: Non-bilious vomiting in preterm neonates discharged from neonatal intensive care units is a common complaint and is often associated with benign conditions such as gastro-oesophageal reflux. A neonate of 27 weeks gestation who presented later with vomiting owing to gastric outlet obstruction is described. He was discharged at 11 weeks of age and required re-admission 1 week later. He had persistent non-bilious vomiting from 7 weeks of age, failure to thrive and metabolic alkalosis. Clinical examination demonstrated visible gastric peristalsis, and hypertrophic pyloric stenosis was suspected. Ultrasound of the gastric pylorus and upper gastro-intestinal contrast studies were negative. Exploratory laparotomy after failure of conservative management revealed a thickened mucosal fold in the gastric pylorus, which was excised. Histopathology demonstrated inclusion bodies which are pathognomonic of cytomegalovirus infection. He was treated with valganciclovir for 6 weeks and was asymptomatic and thriving well at follow-up. Gastric outlet obstruction can be one of the manifestations of CMV infection of the gastro-intestinal tract. Diagnosis can be confirmed only by histopathology. Abbreviations: BPD: bronchopulmonary dysplasia; CMV: cytomegalovirus; H&E: haematoxylin and eosin; IHC: immunohistochemistry; IHPS: infantile hypertrophic pyloric stenosis; NEC: necrotising enterocolitis; PCR: polymerase-chain reaction; VGP: visible gastric peristalsis.